ACCOMPANYING FAMILIES IN CHRONICAL ILL HOSPITALIZATION AT THE SCHOOL HOSPITAL: MEANINGS AND INSTITUTIONAL CONDITIONS. (Fiep Bulletin - online, 2011)
The chronical ill treatment is one of the challenges in the contemporenian society in the field of chemical, scientific and family knowledge. Challenges that indicate keep the patients life with quality. So, the hospitalizations are frequent and need care and companions. The accompanying is of the family that as ax new subjects of the treatment those experiences full of meanings and institutional conditions feasible with that purpose. The purpose of the study is to build a support referential of the family accompanying at the hospital institution. Quanti-Qualitative research conducted from March to August 2010 at the University Hospital of Londrina Parana, with 66 companion families of patients hospitalized in the treatment units. Data collected through interviews with questionnaire and canalized by the statistical method and by the content analysis technique. The data revealed that most of the companians are from Londrina from 41 to 60 years old female predominant... Most of the subje3cts live with the patient and accompany the patient on full time basis have previous experience in accompanying , together with work and to accompany they receive information on the diagnosis to the institutional conditions they stay in the wards accommodated in seats They eat and do hygiene in the hospital. The meanings attributed are related to the protection of the patient, partnership in the care taking, due to the dependence caused by the disease , keep company, participate, inspect and control the treatment.
Keywords: family – chronical disease – hospitalization